Ca‐vacancy effect on the stability of substitutional divalent cations in calcium‐deficient hydroxyapatite. Issue 2 (28th October 2022) - Saito, Tatsushi; Ishikawa, Yuto; Noda, Yusuke; Yokoi, Tatsuya; Oshima, Yu; Nakamura, Atsutomo; Matsunaga, Katsuyuki
Abstract: First‐principles calculations were performed to reveal an effect of Ca vacancies on the stability of substitutional divalent cations M 2+ (M = Mg, Zn, Sr) in Ca‐deficient hydroxyapatite (dHAp). M 2+ concentrations up to 20 mol% in dHAp were considered, and the most stable substitutional sites and their lowest energy configurations in the dHAp lattice were examined with the aid of a generic algorithm method. It was found that defect formation energies of substitutional M 2+ are lower in dHAp than in stoichiometric HAp (sHAp) at all M 2+ concentrations. This indicates that these M 2+ ions are more favorably involved in dHAp than in sHAp, which is in reasonable agreement with experiment. Detailed analyses on atomic structures in dHAp show that the presence of a Ca vacancy varies its surrounding Ca–O bond lengths over a wide area so that Ca–O polyhedrons with various sizes are produced. As a result, M 2+ ions can predominantly occupy Ca sites at which M 2+ fits better, depending on the ionic radii of M 2+ . For Zn 2+ substitution in dHAp, its defect formation energy decreases more with the increasing concentrations and has the minimum value at 15 mol%. Such a trend can be understood from changes in effective coordination numbers of Zn in dHAp.